2021
DOI: 10.32948/auo.2021.10.15
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary renal cell tumors: Clinicopathologic importance

Abstract: Hereditary renal cancer syndromes represent approximately 5% of renal malignancies and have distinctive clinical, histopathologic, and genetic features. Next-generation sequencing and other molecular testing methods have uncovered several hereditary renal cancer syndromes. Several autosomal dominant hereditary renal cell carcinoma (RCC) syndromes, including those related to germline pathogenic variants in VHL, BAP1, MITF, MET, FH, TSC1/TSC2, FLCN, SDH, and CDC73 have been confirmed. FH- and BAP1-related RCCs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 103 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Ongoing studies have demonstrated associations between inherited cancer susceptibility syndromes, RCC, and skin [119,120]. Patients diagnosed with hereditary leiomyomatosis and RCC-associated leiomyomatosis present with a fumarate hydratase gene mutation.…”
Section: Paraneoplastic Syndromes In Rccmentioning
confidence: 99%
See 2 more Smart Citations
“…Ongoing studies have demonstrated associations between inherited cancer susceptibility syndromes, RCC, and skin [119,120]. Patients diagnosed with hereditary leiomyomatosis and RCC-associated leiomyomatosis present with a fumarate hydratase gene mutation.…”
Section: Paraneoplastic Syndromes In Rccmentioning
confidence: 99%
“…This mutation leads to intracellular fumarate accumulation, which mediates proteomic and epigenetic events, ultimately leading to HIF-1 activation. Cutaneous manifestations include multiple cutaneous piloleiomyomas, presenting as firm, reddish-colored papules or nodules [119,120]. Birt-Hogg-Dubé syndrome is a rare autosomal dominant inherited disorder associated with ccRCC and chRCC, caused by point mutations and rearrangements of the folliculin gene.…”
Section: Paraneoplastic Syndromes In Rccmentioning
confidence: 99%
See 1 more Smart Citation